Resolution of Calciphylaxis After Urgent Kidney Transplantation in 3 Patients With End-Stage Kidney Failure - Nordheim, Espen (Transplant Direct, 2016)
BACKGROUND: Calcific uremic arteriolopathy (CUA), also referred to as calciphylaxis, is a rare and serious complication of kidney failure with limited treatment options. Kidney transplantation (KTX) restores kidney function and is hence a potential treatment option for CUA. We present 3 patients who had their CUA lesions successfully healed after urgent KTX. METHODS: Data were retrospectively retrieved from hospital records at our national transplant center. RESULTS: All 3 patients had previously been kidney transplanted and had experienced graft loss and were in stage 5 kidney failure when CUA developed. One patient was on warfarin treatment for pulmonary embolism. Skin lesions developed in the lower limbs in all 3 patients. Multidisciplinary care including intensified hemodialysis did not induce any clinically relevant improvement of the lesions. The recipients were enlisted on a clinically urgent waitlist for KTX and received a deceased donor kidney after 2 to 4 weeks. All recipients experienced good graft function. The lesions healed completely within 6 weeks in 2 patients. In the third patient, partial healing occurred after 2 months and complete healing was achieved 4 months after transplantation. CONCLUSIONS: These cases indicate that urgent KTX may contribute to an efficient treatment for end-stage renal disease patients with CUA.